A mesoporous SBA-15 silica catalyst functionalized with phenylsulfonic acid groups (SBA-15-Ph-SO3H) as a novel hydrophobic nanoreactor solid acid catalyst for a one-pot three-component synthesis of 2H-indazolo[2, 1-b]phthalazine-triones and triazolo[1, 2-a]indazole-triones. Issue 84 (16th September 2015) - Veisi, Hojat; Sedrpoushan, Alireza; Faraji, Ali Reza; Heydari, Masoud; Hemmati, Saba; Fatahi, Behnaz
<x xml:space="preserve">Abstract</x> Phenyl sulfonic acid functionalized mesoporous SBA-15 silica was prepared through the silanization of activated mesoporous SBA-15 with diphenyldichlorosilane followed by silylation and sulfonation.